2013
DOI: 10.4041/kjod.2013.43.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of midfacial asymmetry in patients with nonsyndromic unilateral cleft lip and palate by cone-beam computed tomography

Abstract: ObjectiveTo compare three-dimensionally the midfacial hard- and soft-tissue asymmetries between the affected and the unaffected sides and determine the relationship between the hard tissue and the overlying soft tissue in patients with nonsyndromic complete unilateral cleft lip and palate (UCLP) by cone-beam computed tomography (CBCT) analysis.MethodsThe maxillofacial regions of 26 adults (18 men, 8 women) with nonsyndromic UCLP were scanned by CBCT and reconstructed by three-dimensional dental imaging. The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 26 publications
1
32
0
3
Order By: Relevance
“…Our evaluation of mandibular asymmetry indicated that the mandible was not affected in UCCLP, as more significant asymmetries were detected in the Class I control group. These results accord with previous findings (7,28).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our evaluation of mandibular asymmetry indicated that the mandible was not affected in UCCLP, as more significant asymmetries were detected in the Class I control group. These results accord with previous findings (7,28).…”
Section: Discussionsupporting
confidence: 83%
“…A three-dimensional study of adults revealed no distinctive midfacial hard-or soft-tissue asymmetries between the affected and unaffected sides in individuals with nonsyndromic unilateral cleft lip and palate (7). However, some researchers found greater asymmetry in CLP patients than in controls, particularly in the midface (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beside that, deformity of the nasal rim, including flattening of the nostril of the affected side, is observed. This is a result of the presence of scarring [3,4]. The asymmetry is also observed in hard tissues and refers mainly to the dentoalveolar region that is retruded and rotated backwards at the affected side [3][4][5].…”
mentioning
confidence: 99%